Competitiveness and determinants of Indonesia's natural rubber exports in main partner countries - Ely Tiyastuti; Sri Marwanti; Rhina Uchyani Fajarningsih (Наукові горизонти, 2023)
The main destination countries play an important role in Indonesia's natural rubber exports, as most of Indonesia's natural rubber is exported to these countries. The purpose of this study was to examine the comparative advantage and determinants of Indonesia's natural rubber exports to major partner countries. The RCA (Revealed Comparative Advantage) index is used to assess the comparative advantage, and panel data regression analysis is used to analyze the determinants of exports to the main partner countries (USA, China, Japan, India, Republic of Korea, Brazil, Canada, Germany, Belgium and Turkey). The results of this study indicate that Indonesian natural rubber has a comparative advantage in the main partner countries, which are characterized by RCA index >1. In addition, it was determined that based on panel data regression, the increase in the world price of natural rubber and export restriction policies have led to a decline in natural rubber exports from Indonesia. It is found that the population of Indonesia reduces exports, while the population of partner countries increases exports due to population growth, which will increase the consumption of natural rubber. On the other hand, the increase in Indonesia's gross domestic product (GDP) will lead to an increase in natural rubber production capacity, which will contribute to an increase in exports. It is found that the previous year's demand was also taken into account by partner countries that import Indonesian natural rubber. The results of this study can be useful for the Indonesian government and stakeholders (such as natural rubber producers and exporters) to identify strategies to improve export performance